SO042WHOLE GENOME SEQUENCING OF HUMAN KIDNEY PROGENITORS IDENTIFIES A MUTATION-PRONE CELL TYPE IN THE PROXIMAL TUBULE. (6th June 2020) - Franco, Irene; Helgadottir, Hafdis; Moggio, Aldo; Larsson, Malin; Vrtacnik, Peter; Johansson, Anna; Norgren, Nina; Lundin, Pär; Mas-Ponte, David; Nordstrom, Johan; Lundgren, Torbjörn; Stenvinkel, Peter; et al.
Abstract: Background and Aims: The genome of every cell accumulates somatic mutations while aging. Somatic mutation data can be used to track a cell´s exposure to mutagens, thereby allowing the discovery of cell types that are more susceptible to mutate and become cancer and the underling mechanisms. Method: To detect somatic mutations in healthy, human kidney, we set up a protocol for whole genome DNA sequencing of single non-cancer cells. The protocol requires in vitro clonal expansion prior to sequencing, a step that restricts the analysis to cells able to proliferate in vitro (progenitors), but allows a gene expression analysis in addition to genome sequencing. Cells were obtained from six living kidney donors undergoing surgery. In addition to the kidney cortex biopsy, multiple control tissues (skin, subcutaneous fata and visceral fat) were obtained from each donor, allowing a well-controlled comparison of mutation landscapes in different cell types. Donors´ age spanned from 30 to 69. Results: Somatic mutation and gene expression data showed that we were able to culture two different populations of CD133/CD24 positive, tubular cells. One population showed a low amount of somatic mutations and a mutation profile similar to progenitors from other tissues (fat, skeletal muscle and blood), consistent with a lack of exposure to mutagens. Conversely, the other population showed high mutation burden and a unique mutation landscape, characterized by mutation enrichment in active chromatin, regulatory, and transcribed regions. Accumulation of potential, cancer-driver mutations was 6-fold faster in these compared to control cells. The mutation profile was similar to that of the most common kidney cancer subtypes (clear cell- and papillary cell-carcinoma) and indicated that these cells originated from the proximal tubule, in agreement with gene expression data. Conclusion: Our somatic mutation data from single genomes support the existence of two different populations of proliferating tubule cells in healthy, human kidney. One is protected from mutagen exposure, similar to stem cells from other organs. The other population is derived from damaged proximal tubule cells and shows a high mutation rate between 30 and 70 years of age. Mutations are enriched in transcribed genes and regulatory regions, thus enhancing the chances of tumorigenic transformation and suggesting conditions that predispose to cancer in the kidney proximal tubule.